A combination of beta‐sitosterol and beta‐sitosterol glucoside and normal function of the immune system: evaluation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (24th July 2019) - ,; Turck, Dominique; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Kearney, John; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; et al.
Abstract: Following an application from Essential Sterolin Products (Pty) Ltd., submitted for authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of the Netherlands, the European Food Safety Authority (EFSA) Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to a combination of beta‐sitosterol and beta‐sitosterol glucoside and normal function of the immune system. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The food proposed by the applicant as the subject of the health claim is a combination of beta‐sitosterol and beta‐sitosterol glucoside in a ratio 100:1. The Panel considers that a combination of beta‐sitosterol and beta‐sitosterol glucoside in a ratio 100:1 is sufficiently characterised. The claimed effect proposed by the applicant is 'normal function of the immune system by restoring balance between TH 1‐TH 2 mediated immunity'. The Panel notes that the claimed effect 'normal function of the immune system by restoring balance between TH 1‐ and TH 2‐mediated immunity' does not refer to a specific function of the body which can be assessed in vivo in humans by generally accepted methods, but rather to a mechanism of action by which the food/constituent could exert the claimed effect. The Panel considers that the claimed effect does not refer to any specific health claim as required by Regulation (EC) No 1924/2006. The Panel concludes that a cause and effect relationship cannot be established between the consumption of a combination of beta‐sitosterol and beta‐sitosterol glucoside in a ratio 100:1 and a beneficial physiological effect.